Florida Fertilizer Usage Statistics - Travis W. Shaddox; Joseph Bryan Unruh (EDIS)
Nutrient applications are often required to meet Florida’s demand for agricultural and horticultural commodities, but often those applications occur in close proximity to water bodies. In order for scientists, policy makers, and citizens to make decisions regarding nutrient issues in Florida, it is important to first understand which markets contribute to Florida’s fertilizer consumption. This three-page fact sheet explains Florida’s fertilizer usage statistics. Written by T.W.Shaddox and published by the Environmental Horticulture Department.http://edis.ifas.ufl.edu/ep541